2015
DOI: 10.1515/jbcpp-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of anticholinesterase and NADH oxidase inhibitory activities of an edible fern, Diplazium esculentum

Abstract: Results indicated that 70% methanolic extract of D. esculentum effectively inhibited the enzymes acetylcholinesterase and NADH oxidase and acted as a potent antioxidant and free radical scavenger. These in vitro assays indicate that this plant extract is a significant source of natural antioxidants, which may be helpful in preventing the progression of various neurodegenerative disorders associated with oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Various pharmacological properties of D. esculentum were previously reported [ 29 ]; however, none concentrated on BACE-1 inhibition. Nevertheless, its aqueous leaf extract significantly elevated locomotor activity and stimulated the central nervous system (CNS) in mice [ 30 ], while a 70% ( v / v ) methanolic extract inhibited AChE with an IC 50 value of 0.27 mg/mL [ 31 ], suggesting its potential as a source of anti-AD agents.…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacological properties of D. esculentum were previously reported [ 29 ]; however, none concentrated on BACE-1 inhibition. Nevertheless, its aqueous leaf extract significantly elevated locomotor activity and stimulated the central nervous system (CNS) in mice [ 30 ], while a 70% ( v / v ) methanolic extract inhibited AChE with an IC 50 value of 0.27 mg/mL [ 31 ], suggesting its potential as a source of anti-AD agents.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of the study indicated that "pucukpaku" showed protective effects (62.9%) against cognitive decline. The anticholinesterase and NADH oxidase inhibitory activities of a methanolic extract of D. esculentum have been evaluated [83]. Recently, most of the studies reported that the inhibition of anticholinesterase has been shown to be a strategy for the treatment of neurodegenerative disorders.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“… Relanodi Herb Leaves, stem Vertigo Antipsychotic properties [ 101 , 139 ] Athyriaceae Diplazium esculentum (Retz.) Sw Dhekishak Fern Leaves Headache, epilepsy, paralysis Cholinesterase and NADH oxidase inhibition [ 106 , 118 , 140 ] Begoniaceae Begonia silhetensis (A.DC.) C.B.Clarke Goni kanti Herb Leaves Headache NRE [ 89 ] Bignoniaceae Campsis radicans (L.) Seem Egro (Ma) Vine Leaves Headache (Ma) NRE [ 99 ] Crescentia cujete L. Jummu makal Tree Bark, fruit Brain disorder (Mental disorder) CNS depressant [ 141 , 142 ] Oroxylum indicum (L.) Benth.…”
Section: Introductionmentioning
confidence: 99%